2023
DOI: 10.1126/science.abj9090
|View full text |Cite
|
Sign up to set email alerts
|

Exon architecture controls mRNA m 6 A suppression and gene expression

Abstract: N 6 –methyladenosine (m 6 A) is the most abundant mRNA modification and plays crucial roles in diverse physiological processes. Utilizing a Massively Parallel Assay for m 6 A (MPm 6 A), we discover that m 6 A specificity is globally regulated by “suppressors” that prevent m 6 A deposition in unmethylated transcriptome regions. We identify Exon Junction Complexes (EJCs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
85
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(93 citation statements)
references
References 79 publications
7
85
1
Order By: Relevance
“…In this axis, inhibiting the expression level of m 6 A eraser FTO and m 6 A reader YTHDF2 or inducing the expression level of m 6 A writer like METTL3 may be a feasible treatment method of ESCC. In addition, as mentioned before, P. Cody He et al recently identified EJCs as m 6 A suppressors, which could inhibit the m 6 A methylation of exon junction-proximal RNA within coding sequences [4]. This epoch-making discovery significantly supplements the current understanding of m 6 A methylation progression, which may provide some new regulating methods of m 6 A level in lncRNAs.…”
Section: Diagnostic and Therapeutic Applications Of M 6 A-modified Ln...mentioning
confidence: 75%
See 1 more Smart Citation
“…In this axis, inhibiting the expression level of m 6 A eraser FTO and m 6 A reader YTHDF2 or inducing the expression level of m 6 A writer like METTL3 may be a feasible treatment method of ESCC. In addition, as mentioned before, P. Cody He et al recently identified EJCs as m 6 A suppressors, which could inhibit the m 6 A methylation of exon junction-proximal RNA within coding sequences [4]. This epoch-making discovery significantly supplements the current understanding of m 6 A methylation progression, which may provide some new regulating methods of m 6 A level in lncRNAs.…”
Section: Diagnostic and Therapeutic Applications Of M 6 A-modified Ln...mentioning
confidence: 75%
“…1). Most recently, P. Cody He et al identified exon junction complexes (EJCs) as m 6 A suppressors that prevented the m 6 A methylation of exon junction-proximal RNA within coding sequences, which significantly supplemented the current understanding of m 6 A methylation progression [4]. With the deepening of the research on the role of m 6 A methylation, studies have shown a close relationship between m 6 A methylation and multiple diseases including cancer, major depressive disorder, autism spectrum…”
mentioning
confidence: 99%
“…Besides these conventional modifications, RNA modification as a novel epigenetic modification has been intensely investigated in recent years 54,55 . RNA m6A, the most abundant mRNA modification, is reported to be associated with the mRNA stability, transport, and translation 56,57 . The main epigenetic modifications are summarized in Figure 2.…”
Section: Epigenetic Modificationsmentioning
confidence: 99%
“…METTL3 is the indispensable catalytic enzyme that transfers the methyl group from S-Adenosylmethionine (SAM) to N6 adenine [13]. This process is precisely coordinated with Exon Junction Complexes (EJCs) to provide specificity of m 6 A deposition [14]. METTL3mediated m 6 A modification on chromatin-associated RNA promotes the formation of DNA:RNA hybrids, which have been widely found in many activated regulatory chromosomal loci and G-rich sequences such as telomeres and centromeres [15].…”
Section: Writersmentioning
confidence: 99%